2022
DOI: 10.1371/journal.pone.0274107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and consequences of non-adherence to an evidence-based approach for incidental pulmonary nodules

Abstract: Importance Distinguishing benign from malignant pulmonary nodules is challenging. Evidence-based guidelines exist, but their impact on patient-centered outcomes is unknown. Objective To understand if the evaluation of incidental pulmonary nodules that follows an evidence-based management strategy is associated with fewer invasive procedures for benign lesions and/or fewer delays in cancer diagnosis. Design Retrospective cohort study. Setting Large academic medical center. Participants Adults (≥18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Of greater concern, 35% percent of patients referred for surgical resection had benign disease and the rate of surgical resection was similar among those with low, intermediate, or high-risk nodules, suggesting clinicians did not always follow guideline directed care. These observations have been reinforced in a report from a large academic center, which showed that 1 in 5 incidentally identified PNs did not receive guideline concordant care [ 18 ]. The recent CHEST guidelines on lung cancer screening confirmed these findings in a compilation of prospective lung cancer screening studies [ 19 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of greater concern, 35% percent of patients referred for surgical resection had benign disease and the rate of surgical resection was similar among those with low, intermediate, or high-risk nodules, suggesting clinicians did not always follow guideline directed care. These observations have been reinforced in a report from a large academic center, which showed that 1 in 5 incidentally identified PNs did not receive guideline concordant care [ 18 ]. The recent CHEST guidelines on lung cancer screening confirmed these findings in a compilation of prospective lung cancer screening studies [ 19 ].…”
Section: Discussionmentioning
confidence: 92%
“…It is remarkable that the invasive procedures on patients with benign nodules in this study are lower compared to prior reports. For example, the rates of procedures in the Tanner study were 41% and the current rates are only 19% and 5% for the control and IC tested groups respectively [ 18 ]. Similarly, the rates of malignant nodules routed to CT surveillance are also lower in this study.…”
Section: Discussionmentioning
confidence: 99%